Guided Imagery To Reduce Insomnia in Elderly - Srinalesti Mahanani (Universitas STRADA Indonesia, 2020)
One of the actions that can be given to improve sleep quality in elderly with insomnia is Guided Imagery Therapy. The long term goal of research was to determine the effect of Guided Imagery Therapy against Insomnia In Kota Wilayah Utara Public Health Center Kediri. The design in this research was Pre Experiment Design of Pre-Post Test Design. The population were all elderly who have insomnia with sample number that is equal to 36 respondents, data retrieval by using purposive sampling technique. The collection of data for measurement using a questionnaire of Insomnia Rating Scale. The data was analyzed by using statistical test of Wilcoxon Signed Rank Test, p = 0.000 and z score = 4.054. There are 9 (nine) respondents declined Insomnia Rating Scale after therapy. This proves that the Guided Imagery can reduce Insomnia in the Elderly in Kota Wilayah Utara Public Health Center Kediri.